2006
DOI: 10.3892/or.15.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of nuclear lamins in normal and cancerous prostate tissues

Abstract: The process of carcinogenesis is characterized by definite changes in the protein composition of the nuclear matrix. We have recently found that lamins form, in addition to the nuclear lamina, an intranuclear web of thin fibrils. This finding prompted us to address the question of whether changes in the expression of lamins occur in the course of tumor development. In prostate cancer, lamin B undergoes a significant increase; interestingly, its nuclear content strongly correlates with tumor differentiation. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 19 publications
1
41
0
Order By: Relevance
“…Further lamin B1 has been seen to be affected in prostate [39,46], cervical and uterine cancers [39]. To the best of our knowledge, we are the first group to present clinical data regarding the role of lamin A/C in human breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…Further lamin B1 has been seen to be affected in prostate [39,46], cervical and uterine cancers [39]. To the best of our knowledge, we are the first group to present clinical data regarding the role of lamin A/C in human breast cancer.…”
Section: Discussionmentioning
confidence: 95%
“…However, other studies found the presence of signiWcant amounts of lamins A/C in similar skin cancers (Tilli et al, 2003). The expression of lamins A/C is also reduced in gastrointestinal tract neoplasms including adenocarcinoma of stomach and colon, squamous and adenocarcinoma of the esophagus (Moss et al, 1999), lung cancer including small cell lung cancer (SCLC) but not non-SCLC (Broers et al, 1993;, testicular germ cell tumors , and cancerous prostate tissues (Coradeghini et al, 2006).…”
Section: Lamins Expression Patterns In Other Malignanciesmentioning
confidence: 97%
“…[82][83][84] Loss of A-type lamins results in reduced nuclear stiffness and increased nuclear fragility, 27,33 leading to increased cellular sensitivity to mechanical stress, which can cause further defects in nuclearcytoskeletal coupling, 73,85 mechanotransduction signaling, 7 tissue regeneration, 73,85,86 cell proliferation, 73 and cell differentiation. 25,77,87 However, the majority of human LMNA mutations linked to muscular dystrophies are autosomal dominant, 79 suggesting dominant negative effects of those mutations. Interestingly, most mouse models (eg, lmnaH222P, lmnaN195K) require homozygous expression of the mutant lamin to elicit a phenotype, 84 although a recent report indicates that haploinsufficiency in lmna ϩ/Ϫ mice results in late-onset dilated cardiomyopathy.…”
Section: Laminopathies: Diseases Associated With Nuclear Structurementioning
confidence: 99%
“…For example, lamins A and C are overexpressed in ovarian cancers compared with control cells, 148 and increased levels of lamin B in prostate cancer strongly correlate with tumor differentiation. 87 Importantly, changes in nuclear stiffness can serve as indicator for increased mobility of tumor cells and metastasis potential. 149,150 As discussed earlier, decreased nuclear stiffness through the loss of lamin A/C and lobation may aid neutrophils and other cells to squeeze between endothelial cells during extravasation.…”
Section: Nuclear Shape and Cell Specializationmentioning
confidence: 99%